Acute and transient psychotic disorders: A review of Indian research - Sandeep Grover; Sanjana Kathiravan (Indian Journal of Psychiatry)
Background: Acute and transient psychotic disorder (ATPD) was recognized as separate from other psychotic disorders and described in the International Classification of Diseases (ICD) tenth revision for the first time. A lot of research on ATPD has been conducted in India over the last six decades, but a review focusing exclusively on Indian research on ATPD is not available. Aim: This paper aims to review the literature on ATPD emerging from India. Methodology: A combination of search terms “Acute and Transient Psychosis,” “acute psychosis,” “non-affective psychosis,” “non-affective psychotic disorder,” “reactive psychosis,” “first-episode psychosis,” and “India” were searched on various search engines like PUBMED, Medknow, Hinari, and Google Scholar. We also did a hand search for additional relevant articles, including published abstracts of the Indian Journal of Psychiatry from 2007 to 2023. Relevant papers were selected. Results: The prevalence of ATPD varies across different study settings, and it tends to have an abrupt to acute onset, and is primarily associated with stress. Few studies have assessed the subtypes of ATPD, and symptom profile has been inconsistently reported. There is a lack of trials on the effectiveness or efficacy of antipsychotics in ATPD patients. In a large proportion of patients initially diagnosed with ATPD, the diagnosis remains stable, with recurrence varying from 10% to 46.6% based on the duration of follow-up. Conclusion: There is a need for more multicentric studies, studies with larger sample sizes, and consistency in data about risk factors. There is a need to evaluate symptom profile, course, outcome, and treatment outcomes in patients with ATPD using validated instruments to improve our understanding. Further, there is a need for comparative studies to evaluate the risk factors for ATPD.